The Stalagmite Record of Southern Arabia: Climatic Extremes, Human Evolution and Societal Development - Nicholson, Samuel Luke; Jacobson, Matthew J.; Hosfield, Rob; Fleitmann, Dominik (Frontiers in Earth Science, 2021)
The fluctuating climatic conditions of the Saharo-Arabian deserts are increasingly linked to human evolutionary events and societal developments. On orbital timescales, the African and Indian Summer Monsoons were displaced northward and increased precipitation to the Arabian Peninsula which led to favourable periods for human occupation in the now arid interior. At least 4 periods of climatic optima occurred within the last 130,000 years, related to Marine Isotope Stages (MIS) 5e (128-121 ka BP), 5c (104-97 ka BP), 5a (81-74 ka BP) and 1 (10.5-6.2 ka BP), and potentially early MIS 3 (60-50 ka BP). Stalagmites from Southern Arabia have been key to understanding climatic fluctuations and human-environmental interactions; their precise and high-resolution chronologies can be linked to evidence for changes in human distribution and climate/environment induced societal developments. Here, we review the most recent advances in the Southern Arabian Late Pleistocene and Early Holocene stalagmite records. We compare and contrast MIS 5e and Early Holocene climates to understand how these differed, benchmark the extremes of climatic variability and summarise the impacts on human societal development. We suggest that, while the extreme of MIS 5e was important for H. sapeins dispersal, subsequent, less intense, wet phases mitigate against a simplistic narrative. We highlight that while climate can be a limiting and important factor, there is also the potential of human adaptability and resilience. Further studies will be needed to understand spatio-temporal difference in human-environment interactions in a climatically variable region.